Renal Health Benefits of Rural City Planning in Japan - Nagai, Kei; Koo Yuk Cheong, Daniel; Ueda, Atsushi (Frontiers in Nephrology, 2022)
Progression of chronic kidney disease (CKD) is a substantial threat because it is associated with reduced healthy life expectancy and quality of life, and increase in economic burden. Research indicates people with nondialysis CKD often have lower physical functioning and that improvement of physical activity may contribute to maintaining renal health. Another issue with the current treatment of CKD is that the synergistic effects of rural depopulation due to aging and uncontrolled rural city sprawling will increase the number of under-served healthcare areas. To ensure the quality of renal health care, hospital integration is desirable, under the condition of reconstruction of the public transport system for physically and socially vulnerable people. Recently, medical and non-medical scientists advocate the challenge of city planning for population health. The links between city design and health such as cardiovascular disease, obesity, type 2 diabetes and mental disorders, have been widely studied, except for renal health. Based on our experience in a Kidney and Lifestyle-related Disease Center, we propose the idea that city planning be prioritized to improve renal health through two main streams: 1) Improve physical status by use of public and active transportation including daily walking and cycling; and 2) Equal accessibility to renal health services. Many countries, including Japan, have enacted plans and public policy that encourage increased levels of physical activity. We should focus on the impact of such movement on renal as well as general health.